The Relationship Between Polymorphic Fibroblast Growth Factor Receptor (FGFR) Gene and Breast Cancer Risk - Hosseini, Mojgan (Archives of Breast Cancer, 2017)
Background: Genetic factors associated with cancer have been widely investigated and several polymorphisms have been connected with breast cancer. Breast cancer (BC) can be considered one of the most popular reasons of death among women. BC, likewise, is the second cause of death in Iran. The present research aims at determining the frequency of the ?broblast growth factor receptor (FGFR) gene polymorphism in patients with breast cancer. Methods: The FGFR family is one of the tyrosine kinase receptors containing 4 members, whose pathway is activated in many tumors. We assessed, for the first time, these polymorphisms and their consequences on the breast cancer risk association in an Iranian sporadic population-based case-control study including 126 patients with breast cancer and 160 controls using a PCR-RFLP-based assay. Results: The analyses of the experimental and control groups indicated that homozygote genotype FGFR4 Gly/Gly has the highest frequency in experimental and control groups (30.4% and 18.9%). The main genotype FGFR4 Gly/Gly risk factors in our population were: ArgGly /GlyGly, OR = 2.359, 95% CI = 0.208 - 4.621, P = 0.001; ArgArg /ArgGly, OR = 0.412, 95% CI = 0.082 - 0.547, P = 0.078, ArgArg /GlyGly, OR = 0.076, 95% CI = 0.030 - 0.189, P = 0.26. Conclusions: A significant association was observed between breast cancer risk and FGFR4 GlyGly and ArgGly polymorphism.